Spatial distribution of Batrachochytrium dendrobatidis in South American caecilians - Lambertini, Carolina; Guilherme Becker, C. [UNESP]; Bardier, Cecilia; Leite, Domingos da Silva; Toledo, Luis Felipe (Inter-research, 2017)
The amphibian-killing fungus Batrachochytrium dendrobatidis (Bd) is linked to population declines in anurans and salamanders globally. To date, however, few studies have attempted to screen Bd in live caecilians; Bd-positive caecilians have only been reported in Africa and French Guiana. Here, we performed a retrospective survey of museum preserved specimens to (1) describe spatial patterns of Bd infection in Gymnophiona across South America and (2) test whether areas of low climatic suitability for Bd in anurans predict Bd spatial epidemiology in caecilians. We used quantitative PCR to detect Bd in preserved caecilians collected over a 109 yr period, and performed autologistic regressions to test the effect of bioclimatic metrics of temperature and precipitation, vegetation density, and elevation on the likelihood of Bd occurrence. We detected an overall Bd prevalence of 12.4%, with positive samples spanning the Uruguayan savanna, Brazil's Atlantic Forest, and the Amazon basin. Our autologistic models detected a strong effect of macroclimate, a weaker effect of vegetation density, and no effect of elevation on the likelihood of Bd occurrence. Although most of our Bd-positive records overlapped with reported areas of high climatic suitability for the fungus in the Neotropics, many of our new Bd-positive samples extend far into areas of poor suitability for Bd in anurans. Our results highlight an important gap in the study of amphibian chytridiomycosis: the potential negative impact of Bd on Neotropical caecilians and the hypothetical role of caecilians as Bd reservoirs.
Keywords: Chytrid infection dynamics; Gymnophiona; Life history; Environmental variables; Museum specimens